More Goals, Fewer Babies? On National Teams' Performance and Birth Rates - Luca Fumarco; Francesco Principe (Institute of Labor Economics (IZA), 2021)
Does national team performance boost birth rates? We compiled a unique dataset combining country-level monthly birth rates for 50 European countries, along 56 years, with measures of national teams' performance in 27 international football events. We find that an increase in national teams' performance in international cups is associated with a drop in birth rates nine months after the event. We hypothesize that these results might be explained by individuals' time allocation choices.
Keywords: I10; J10; J11; J13; 330; football; sporting events; time allocation; birth rates; fertility